Teletandem mediation on Facebook - Nogueira de Moraes Garcia, Daniela; Gomes de Souza, Micheli (Revista do GEL, 2018)
Teletandem is a telecollaborative learning context, which involves the process of pairing up language learners of different institutions around the world. Since 2006, institutional teletandem practice has involved the offer of pedagogical mediation to support learners’ development. The mediation aims to provide teletandem participants a context for sharing experience and reflecting on their language and intercultural learning process. This article aims at describing the mediation session procedures and the findings of a study carried out during teletandem interactions between students from Brazil and from the United States. A private Facebook group was used to support the contact between the mediator and students of the Brazilian university. In this work, we present the review of the concept of mediation in teletandem and present the results of an interpretivist qualitative analysis that show that the role of the mediator is focused on providing encouragement and guidelines based on teletandem theory and principles. We also point out the study limits and propose some possibilities for future research that might focus on mediation sessions through virtual platforms or social networks.